Study On Analysis Of Pre-Marriage Couple's Perceptions Of Partnership Gender In The Domestic Areas In Yogyakarta - Khasanah, Nur; Riska, Herliana; Santika, Ni Kadek Giri (Pusat Studi Gender Universitas Jember, 2024)
The COVID-19 pandemic, which has occurred, followed by a global crisis and the issue of recession in various parts of the world, including Indonesia, has had a vulnerable impact on family resilience. This can be seen from the phenomenon of a significant increase in the prevalence of divorce from 291,677 in 2020, which increased by 53% to 447,743 in 2021, which places Indonesia as the country with the highest prevalence of divorce in Asia-Africa. This is directly proportional to the high prevalence of single parents, which places Indonesia in the second-highest position in the world with fatherless countries and DI. Yogyakarta ranks third highest in Indonesia. According to the Indonesian Ministry of Religion, the phenomenon of divorce is dominated by contested divorce from wives, namely 73.7%, with the reason being ongoing disputes at 62.4%. Various factors, including gender inequality in the domestic sphere, cause the disputes. The research method used was qualitative, with an explanatory research approach to 34 informants who were prospective premarital couples in the KUA Depok Yogyakarta work area. Data was collected through FGDs and deep interviews to explore prospective partners' perceptions of gender partnership in the family—purposive sampling technique according to inclusion criteria. Data analysis uses phenomenological studies, including data familiarization through identifying thematic frameworks, data indexation, coding and charting, and data interpretation carried out independently by the researcher. The research results show that the lowest knowledge of respondents regarding family functions is the socio-cultural function, namely ten respondents (29.41%), followed by the coaching function, namely 14 respondents (41.17%), and the reproductive function, namely 16 respondents (47.06%).